A Review: Are Maternity Orthoses Effective? - Usama Bin Yar (Journal of University Medical & Dental College, 2023)
ABSTRACT Purpose of Review: Maternity orthoses (MO) are extensively accessible, frequently recommended, and widely used to relieve pelvic girdle pain (PGP) and lower back pain (LBP) during pregnancy. The aim of this study is to perform a literature evaluation on the outcomes of utilizing MO as the exclusive intervention for improving women’s comfort during pregnancy. Recent Findings: The included studies yielded four outcomes: pain relief, balance enhancement, functional assistance and mobility improvement. More than 200 publications were reviewed, with no material published before 2015. This study also presents knowledge of the impacts and effectiveness of using MO as the only intervention for improving pregnancy comfort, as well as information regarding the many types of MO which are commonly available. As a result, instruction about the use of belts and follow-up of usage of the belt during and after pregnancy can be found to be vital in the care of misaligned pelvic in women. The findings might be utilized to promote the beneficial usage of MO throughout the perinatal to the postpartum period. Summary: This research provides knowledge of the effects and efficacy of using MO as a solitary intervention for improving pregnancy comfort and information on the many types of MO and the characteristics that may impact orthoses usage. Furthermore, utilizing MO for an incredible duration might impede child growth due to a lack of capacious room in the womb due to external pressure. This important factor should be explored more with physiological experimentation and reported accordingly to describe the effectiveness of MO and its effects on the womb.